(untitled) (World Bulletin of Public Health, 2023)
Currently, diseases of the thyroid gland (thyroid gland) in their prevalence occupy the first place among endocrine pathology. According to the results of the largest epidemiological studies, the prevalence of hypothyroidism in women is 4-21% and 3-16% in men and is characterized by a significant increase in its frequency among older people [4,5]. In women, subclinical hypothyroidism occurs 2 - 2.5 times more often than in men. The prevalence of subclinical thyrotoxicosis, according to various studies, varies from 0.6% to 3.9%, depending on the sensitivity of the method used to determine TSH and the iodine supply of the region. The prevalence of diffuse toxic goiter in the general population is relatively high and reaches 1-2%